Aliran Pendidikan Islam Tradisionalis-Tekstualis (Studi Pemikiran Al-Qabisi) - Muhyidin Muhyidin (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2013)
Abstract: In the history of civilization, Islam produced many great thinkers and leading scholars in various fields, such as education. Among Muslim thinkers who wrestled in education is al-Qabisi. Educational thought and al-Qabisi represent and reinforce the philosophy of life and socio-cultural conditions of society in his day who is a religious social environment, where atheism and materialism not obtain a place, while the al-Quran and prayer has become an indispensable part of people’s lives. By looking at these facts, it is understandable that there is the impression and feel a very strong religious education in mind, so Muhammad Jawwad Ridla put into groups of religious education stream conservative or traditional-textual. Although the label is pinned on educational thought al-Qabisi is a traditional-textual, this study proves that many of the items thinking that al-Qabisi contextual and still remain in accordance with the conditions today, for example, his concept of the active learning strategies, peer teaching , exemplary methods of moral education, the principle of equality in education, love approach in education, and also about the ethics of the teaching profession. Keywords : al-Qabisi, thought, traditionalists, textualist.